Analisis Pengaruh Retribusi Daerah, Jumlah Penduduk dan Tingkat Partisipasi Angkatan Kerja Terhadap Pendapatan Asli Daerah Kota Malang - Aditya Ananta Ashari; Ririt Iriani S (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Original Regional Income is income collected by the region which is very important as a source and benchmark for financing in accordance with legal regulations. This research is to analyze the influence of Regional Levies, Population Number, and Labor Force Participation Level on Original Regional Income in the Malang City Region. In this research, the Classic Time Series Assumption Analysis uses secondary data originating from BPS Malang City for 2010-2022 using the Quantitative method. The results obtained in this research are that the Population Number and Participation Rate of the Work Force have a positive influence on the Regional Original Income product of Malang City, while the Regional Levy is known to have an insignificant influence on the Regional Original Income in Malang City.